1995
DOI: 10.1159/000282758
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Calcium Oxalate Urinary Lithiasis: Usefulness of Parks’ and Tiselius’ Indices in the Evaluation of the Risk of Stone Formation

Abstract: Different indices of the risk of urinary calcium oxalate crystallization were compared to determine their usefulness in detecting the stone-formers particularly prone to recurrence. Urine volume and calcium, oxalate, citrate, magnesium or creatinine were determined in 55 patients presenting with an idiopathic calcium oxalate urolithiasis, as well as in 50 control subjects. On 24-hour urine samples, these elements allowed for the calculation and comparison of different indices of lithogenous risk as proposed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…23 In the present study, the mean values of urinary calcium, oxalate and uric acid excretion were significantly higher in patients with RSF than in subjects with NSF. Hypercalciuria and hyperoxaluria are well-known risk factors of renal calcium oxalate stone formation, 24,25 and these factors might contribute more to renal stone disease rather than hypocitraturia in patients with RSF. Ogawa et al demonstrated that 24-h urinary citrate excretion was not positively associated with calcium oxalate supersaturation (DG[CaOx]).…”
Section: Discussionmentioning
confidence: 99%
“…23 In the present study, the mean values of urinary calcium, oxalate and uric acid excretion were significantly higher in patients with RSF than in subjects with NSF. Hypercalciuria and hyperoxaluria are well-known risk factors of renal calcium oxalate stone formation, 24,25 and these factors might contribute more to renal stone disease rather than hypocitraturia in patients with RSF. Ogawa et al demonstrated that 24-h urinary citrate excretion was not positively associated with calcium oxalate supersaturation (DG[CaOx]).…”
Section: Discussionmentioning
confidence: 99%
“…This program has remained the "gold standard" since 1977. We have been unable to find any reports of a program that either refutes or is comparable to the Equil2 program, although we know some researchers strongly support the indices of Parks and Tiselius [23], which seem to be as useful clinically as Equil2 [24].…”
Section: Calcium Oxalate Supersaturationmentioning
confidence: 80%